Democratic Algorithms - Poechhacker, Nikolaus (meson press, 2024)
Can an algorithm be democratic? And how can we understand algorithms not only as technical, but also as social and political phenomena? Democratic Algorithms offers theoretically and empirically informed perspectives on how we can imagine and design algorithms for a democratic society, and what we even mean by that. Based on ethnographic fieldwork, the book illustrates how a recommender system was built in a public broadcaster, raising questions not only about organizational and technical implementation, but also about the possible compatibility of such an algorithmic system with democratic constitutions.